Ethnolinguistic influence on citation in English and Persian hard and soft science research articles - Shooshtari, Zohreh Gooniband; Jalilifar, Alireza; Shahri, Somaiyeh (Penerbit Universiti Kebangsaan Malaysia, 2017)
Citation, as a central and integral issue in academic writing, has been the focus of many recent scholarly articles to highlight the significant role of this discursive practice in the realm of research article writing. Nonetheless, most of the previous studies, with notable exceptions, examined disciplinary influences on citation practices independently of ethnolinguistic influences, and vice versa. The present study investigates the doubly contrastive language-discipline perspective on the one hand and draws a distinction between disciplinary cultures and national cultures on the other. A corpus of 240 research articles sampled from leading Persian and English language medium journals of applied linguistics and psychology as representatives of soft sciences, and computer engineering and mechanical engineering as representatives of hard sciences, was examined drawing on Coffin‟s (2009) integrative analytic framework. Quantitative and qualitative analyses of the several aspects of citation features of Bakhtinian dialogism demonstrated some cross-disciplinary and cross-linguistic similarities and differences. Pedagogical implications derived from these findings are discussed.